Effective interviewing and interrogation techniques - Gordon, Nathan J.; Fleisher, William L. (Academic Press, an imprint of Elsevier, 2019)
Effective Interviewing and Interrogation Techniques, Fourth Edition, answers the question, 'how do you know when someone is lying?' In addition, it also provides a guide for interviewing probable suspects and interrogating likely perpetrators on techniques and tradecraft and presents forensic assessments based on psychophysiology and non-verbal behavior. Topics discussed include the Morgan Interview Theme Technique (or MITT) and the Forensic Assessment Interview (or FAINT). Other chapters address techniques for interviewing children, the mentally challenged, pre-employment interviews, aggressive behavior, and how to deal with angry people. The book concludes by presenting future methods for searching for the truth.